Biobanking of Residual Specimens from Diagnostic Genetic Laboratories: Standard Operating Procedures, Ethical and Legal Considerations, and Research Applications - Grommisch, BS, Brittany; DiAdamo, BS, Autumn J.; Pan, MD, PhD, Xinghua; Ma, MD, PhD, Deqiong; Xu, MS, Zhiyong; Xie, MD, PhD, Jiansheng; Qi, PhD, Yu; Li, PhD, Peining (North American Journal of Medicine and Science, 2013)
Clinical applications of high-throughput technologies such as microarray analysis, next generation sequencing and tandem mass spectrometry have significantly improved the diagnostic performance and research capacity for many genetic diagnostic laboratories. Biobanking of patients’ residual specimens and test records could be a useful resource for further research applications but related technical, ethical and legal issues need to be resolved. In this review, standard operating procedures and laboratory information management system for short-term and/or long term storage of residual original patient specimens and processed patient specimens have been outlined. To comply with current ethical and legal requirements, procedures for case-oriented consent, general informed consent and waiver of consent as well as methods for returning incidental findings and individual research results have been summarized. Diagnostic residual specimens have been used in many research projects to improve clinical quality and to characterize genetic defects for underlying disease-causing mechanisms. The advantages and disadvantages of diagnostic biobanking for research applications have been discussed. A model of ‘Diagnostics-Biobanking-Research-Returning’ is proposed to promote rapid transition and effective collaboration from diagnostic to research and eventually provide better preventive and therapeutic approaches for patients with genetic disorders. [N A J Med Sci. 2013;6(4):200-207. DOI: 10.7156/najms.2013.0604200]